Strategically Constructed Bilayer Tin (IV) Oxide as Electron Transport Layer Boosts Performance and Reduces Hysteresis in Perovskite Solar Cells. Issue 12 (27th May 2019) - Lin, Liangyou; Jones, Timothy W.; Wang, Jacob Tse‐Wei; Cook, Andre; Pham, Ngoc Duy; Duffy, Noel W.; Mihaylov, Blago; Grigore, Mihaela; Anderson, Kenrick F.; Duck, Benjamin C.; Wang, Hongxia; Pu, Jian; et al.
Abstract: Nanostructured tin (IV) oxide (SnO2 ) is emerging as an ideal inorganic electron transport layer in n–i–p perovskite devices, due to superior electronic and low‐temperature processing properties. However, significant differences in current–voltage performance and hysteresis phenomena arise as a result of the chosen fabrication technique. This indicates enormous scope to optimize the electron transport layer (ETL), however, to date the understanding of the origin of these phenomena is lacking. Reported here is a first comparison of two common SnO2 ETLs with contrasting performance and hysteresis phenomena, with an experimental strategy to combine the beneficial properties in a bilayer ETL architecture. In doing so, this is demonstrated to eliminate room‐temperature hysteresis while simultaneously attaining impressive power conversion efficiency (PCE) greater than 20%. This approach highlights a new way to design custom ETLs using functional thin‐film coatings of nanomaterials with optimized characteristics for stable, efficient, perovskite solar cells. Abstract : SnO2 has recently emerged as an attractive n‐type layer for perovskite solar cells, with advantages of high optical transparency, high electron mobility, UV‐stabilized properties as well as low‐temperature processing. Here, a detailed study of structure and morphology of a critical aspect of these devices is reported—the electron transport layer (ETL)—demonstrating improved energy level alignment, reduced hysteresis, and interfacial recombination, which translates to enhanced device performance and stability.